The paleogeographic meaning of the coastal peats of rio grande do sul - de LIMA, Leonardo Gonçalves; Dillenburg, Sérgio; Buchmann, Francisco [UNESP]; Parise, Cláudia (UNESP - Universidade Estadual Paulista, 2020)
In the Coastal Plain of Rio Grande do Sul (PCRGS), peat deposits appear along the coast indicating sectors where coastal barriers exhibit a transgressive nature. Throughout the last decades, many causes are composed to explain the erosive process in these sectors, major associated with natural phenomena. These outcrops are considered as key elements in the understanding of the long term evolution of this coast. The chemical processing of the samples was made in cold mode with HCl (5%) and KOH (5%) and the separation of organic and inorganic particles with aqueous solution of ZnCl2.This study was based on peat samplings from geological surveys, outcrops and Georadar profiles in the beaches of Itapeva and Hermenegildo. The results of this study indicate that the basal layer covering the pleistocene sediments is formed by basal peat, chronologically signaling the beginning of Holocene sedimentation in the PCRGS around 10.000 years BP, when still essentially lacustrine conditions prevailed through the dominance of herbaceous and hydrophitic vegetation where the Holocene coastal barrier systems would develop. Once installed, these barriers created the conditions for the development of a second generation of paludal environments, this time linked to the reduction of the environmental depths during the process of filling since 710 years B.P. The results of the present study provide evidences that the current coastline of the Rio Grande do Sul is in a continuous process of reorientation, led by a sedimentary deficit in the coastal sectors where the retrograde barriers migrate towards the mainland and to the N-NO direction, exposing peat deposits systematically along the coast.
O significado paleogeográfico das turfeiras costeiras do rio grande do sul
Keywords: Coastal Plain; Paleogeography; Peat